Home gardens and in situ conservation of plant genetic resources in farming systems: Proceedings of the second international home gardens workshop, 17-19 July 2001, Witzenhausen, Germany - Watson, J.W.; Eyzaguirre, Pablo B. (2002)
The results of the Home Garden Project presented in these Workshop Proceedings contribute to national and global strategies for including home gardens as a distinct and important component of in situ conservation of agrobiodiversity. The national and comparative studies have also begun to establish a clear link between home garden diversity and household livelihoods and food security. IPGRI will continue to build the global research partnerships that provide national programmes and local organizations with the tools to include genetic resources management at the household and ecosystem levels in national biodiversity conservation and development strategies and policies. We thank the many institutions, communities, and individuals that have contributed to the research on home gardens genetic resources and Germany for its financial support of the Workshop and the research activities.